THE JUSTIFICATION OF THE EFFICIENCY OF FINANCIAL SUPPORT OF EDUCATION IN THE CONTEXT OF THE NATIONAL ECONOMY DEVELOPMENT - A. Vorontsova; T. A. Vasylieva; T. Mayboroda (Фінансово-кредитна діяльність: проблеми теорії та практики)
Abstract. In the conditions of formation of post-industrial social relations, there is a qualitative transformation of basic principles of functioning of both leading national economies and the world economy as a whole. In particular, under intensive scientific and technical progress, as well as the growth of labor productivity, knowledge, technologies and innovations became the basis for building a competitive national economy. Education, as one of the leading industries that produce these factors, becomes one of the highest priorities of state regulation.